Pengaruh Kecerdasan Emosional dan Motivasi Belajar Terhadap Hasil Belajar Matematika Siswa - Tisa Puspita Anggraini; Nurhayati Abbas; Franky Alfrits Oroh; Khardiyawan A.Y. Pauweni (Jambura Journal of Mathematics Education, 2022)
This article discusses the influence of emotional intelligence and learning motivation on students' mathematics learning outcomes with the aim of knowing: 1) the positive direct effect of emotional intelligence on students' mathematics learning outcomes, 2) the positive direct influence of learning motivation on students' mathematics learning outcomes, 3) direct influence positive emotional intelligence on learning motivation. The method used is a survey method using a path analysis model. The sampling technique used is simple random sampling. The collection of data on emotional intelligence and learning motivation was carried out using a questionnaire and data on mathematics learning outcomes using an objective test. The results showed that: 1) there was a positive direct effect of emotional intelligence on students' mathematics learning outcomes of 68.60%, (2) there was a direct positive influence of learning motivation on students' mathematics learning outcomes of 30.90%, (3) there was a direct influence positive emotional intelligence on motivation to learn by 81.60%.